Do the benefits of male circumcision outweigh the risks? A critique of the proposed CDC guidelines - Brian D. Earp (Frontiers Media S.A., 2015)
The Centers for Disease Control and Prevention (CDC) have announced a set of provisional guidelines concerning male circumcision, in which they suggest that the benefits of the surgery outweigh the risks. In this perspective article, I highlight a few of the key scientific and ethical issues worth considering in interpreting the new CDC recommendations.